PLATELET TURNOVER AND ATHEROTHROMBOSIS - A. V. MAZUROV («REMEDIUM GROUP» Ltd., 2017)
Platelets play an important role in initiating atherothrombosis, i.e. the formation of blood clots inside a blood vessel at areas of atherosclerotic vascular injury. The functional (prothrombotic) activity of platelets significantly varies both in healthy individuals and in patients with cardiovascular diseases. The increased platelet production and turnover may be one of the reasons for promoting platelet activity. Stimulating thrombocytopoiesis results in large and reticular (with an increased amount of RNA) "young" platelets in the bloodstream. These platelets contain more adhesive receptors, more secretory granules and have an increased aggregation capacity. The review provides data indicating that large and reticular platelets are not only markers, but also predictors of atherothrombotic events, and primarily of acute coronary syndrome. An increase in such platelet count in patients receiving antiplatelet drugs is associated with a decrease in effectiveness of their antiplatelet action. It is assumed that the appearance of large and reticular platelets in the blood of patients with atherosclerosis and atherothrombosis may be a consequence of an increase in the thrombopoietic activity of megakaryocytes in these pathological conditions.